Zhodnocení a financování investičního záměru - Blažíčková, Věra (Vysoké učení technické v Brně. Fakulta podnikatelská, 2011)
Diplomová práce se zabývá investicí do nákupu nové vodorovné vyvrtávačky v konkrétním podniku působícím v těžkém průmyslu. Obsahuje posouzení finanční situace společnosti, zhodnocení efektivnosti investičního záměru a srovnání konkrétních nabídek leasingových společností a bankovních institucí. Podstatou práce je, na základě získaných informací, zjistit zda investiční záměr realizovat a poté navrhnout vhodný způsob financování.

The diploma paper deals with an investment in the purchase of a new horizontal boring and milling machine at a plant being engaged in heavy industry. The paper contains the assessment of company’s financial position, the evaluation of investment project effectiveness and the comparison of concrete offers submitted by leasing companies and bank institutions. The subject matter of the paper is to find out – on the basis of the information obtained – whether to implement the investment project and then to propose an appropriate manner of financing.
Evaluating and Financing an Investment Project
Keywords: investice; investiční záměr; efektivnost investice; finanční analýza; financování; vlastní peněžní prostředky; úvěr; leasing; investment; investment project; investment effectiveness; financial analyses; financing; own financial resources; credit; leasing